The antecedents of purchase intention on healthy instant noodle products: Is it worth fighting for? - Alamanda, Dini Turipanam; Wibowo, Lili Adi; Disman, Disman; Anggadwita, Grisna (Jurnal Manajemen Indonesia, 2024)
Instant noodles are one of the favorite foods in Indonesia. Many food and beverage companies compete to attract consumer interest by providing promotions for various flavors of instant noodle products. The health issue of instant noodle products has become a concern for business owners who want to provide healthier food. However, the importance of healthy food has yet to receive a positive and significant response from Indonesian consumers. Increasing consumer interest in healthy food in Indonesia is crucial since it can significantly affect public health. This study aims to measure the effect of convenience, advertising, subjective norms, and product attributes as antecedents of people's purchase intention for healthy instant noodle products. This research used a quantitative approach by distributing questionnaires to respondents selected through a purposive sampling technique based on the criteria: consumers of healthy instant noodle products who have previously purchased instant noodles or a variety of healthy instant noodles. A total of 210 respondents participated in filling out this research questionnaire. Partial least squares structural equation modeling (PLS-SEM) was used as an analytical technique. The results of this study indicate that subjective norms are not proven to be an antecedent that affects consumer purchase intentions for healthy instant food products. In contrast, product attributes are the most influential antecedent. This study provides academic implications by adding literature on the antecedents of people's purchase intentions for healthy instant noodle products. The practical implications, especially for business owners, are shown by helpful information to improve campaigns, promotions, and product sales. Keywords—Consumer behavior; Healthy instant noodles; Marketing management; Purchase intention